Calcium and Action Potentials of Bullfrog Sympathetic Ganglion Cells - Koketsu, K. (The Rockefeller University Press, 1969)
Bullfrog sympathetic ganglion cells were capable of producing action potentials (Ca spikes) in an isotonic (84 mM) CaCl2 solution. The peak level of Ca spikes showed an approximately 30 mv increase with a 10-fold increase in the Ca concentration. Na as well as Ca ions were capable of acting as charge carriers during the production of action potentials in a solution containing relatively high Ca and relatively low Na ions. A decrease in the external Ca concentration depressed the maximum rate of rise at a fixed resting potential level, and increased the maximum rate of rise of the Na spikes at a high resting potential level at which Na inactivation was completely depressed. Compared to Na spikes, Ca spikes were less sensitive to TTX and procaine. Ganglion cells were also capable of producing action potentials (Sr spikes) in an isotonic SrCl(2) solution and prolonged action potentials in an isotonic BaCl(2) solution, but these cells were rendered inexcitable in an isotonic MgCl(2) solution. The peak level of the Sr spikes was dependent on the external Sr concentration and was insensitive to both TTX and procaine. Sr ions, like Ca ions, reduced Na inactivation during the resting state, and depressed the maximum rate of rise of the Na spikes at a high resting potential level. It was concluded that Ca (and Sr) ions exert dual actions on the membrane; namely, regulating the Na permeability and acting as charge carriers during the active state of the membrane.